Buddhist Protectionism, Political Imaginaries of Belonging, and Prospects for Covenantal Pluralism in Myanmar - Horstmann, Alexander (The review of faith & international affairs, 2020)
After decades of military rule in Myanmar, civil society organizations and the National League for Democracy (NLD) have used the opening public space to mount inter-religious dialogue and to raise sensibility for religious freedom in an ethnically and religiously diverse nation. At the same time, the new democratic space is also used by well-resourced Buddhist and nationalist organizations and the military in the name of protecting race and Buddhist religion (sasana). The article argues that it is not clear what democracy in Myanmar means and that its contents are highly contested. However, the promotion of covenantal pluralism seems to be a crucial step towards reconciliation, constitutional protection of religious minorities, and long-lasting peace.